Ferric carboxymaltose-induced posterior reversible encephalopathy syndrome: A rare case report - Singh, Amit Shankar; Saini, Deepak; Singh, Arshpreet (Indian Journal of Case Reports, 2026)
Posterior reversible encephalopathy syndrome (PRES) is a neurotoxic condition characterized by acute neurological symptoms and distinctive imaging findings. It is commonly linked to hypertension, immunosuppressants, or chemotherapy, but rarely to intravenous (IV) iron infusion. We describe a 40-year-old female who developed PRES following IV ferric carboxymaltose (1 g) for severe anemia. Soon after infusion, she experienced anaphylactic shock with hypotension, bradycardia, facial swelling, vision loss, headache, and vomiting. Magnetic resonance imaging brain revealed bilateral parieto-occipital hyperintensities on T2/fluid-attenuated inversion recovery sequences, consistent with PRES. Labs showed worsening anemia (hemoglobin 7.4 → 6.3 g/dL), thrombocytopenia, leukocytosis, and a sharp rise in serum iron (362 μg/dL). She was managed with mannitol, levetiracetam, antibiotics, and supportive care. Gradual neurological recovery was observed, with vision improving over 1 week. This report highlights a rare instance of PRES triggered by ferric carboxymaltose. Timely recognition and appropriate treatment are essential to prevent long-term complications. Clinicians should remain vigilant for PRES in patients presenting with acute neurological symptoms after IV Iron therapy.